PENGUKURAN TURBULENSI DAN ANGULARITAS ALIRAN PADA TEROWONGAN ANGIN SUBSONIK LAPAN (THE MEASUREMENT OF TURBULENCE AND FLOW ANGULARITY IN LAPAN’S SUBSONIC WIND TUNNEL) - Hartono, Firman; Bessie, Ronald; Aribowo, Agus (Indonesian Journal of Aerospace, 2016)
This paper explains the measurement of turbulence intensity and angularity in LAPAN’s Open Loop Subsonic Wind Tunnel. The objective of the research is to find out the aerodynamic characterstic of the tunnel. Turbulence intensities were measured using 200 mm and 300 mm diameter turbulence sphere. The flow angularity in the cross section of tunnel’s test section was measured using five holes probe at two different axial position i.e. 1. above internal balance turning table and 2. above external balance turning table. The number of measured points are 110 for every cross section plane and the average velocity during angular flow measurement is 15 m/s. Turbulence measurements shows wind tunnel’s turbulence intensity of 0.26% at 25.9 m/s and 0.1% at 19 m/s. Angularity measurement shows relatively large angular flow variation in the jet, i.e. pitch angle of ±3o and achieving +7o at some locations and yaw angle of ±2.5o.